2006
DOI: 10.1088/0953-2048/19/8/021
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial oxygen mobility in superconducting samples of Bi2Sr2CaCu2O8+y

Abstract: Since high-temperature superconductors were discovered, several studies have been made on their physical properties, attempting to associate them to the origin of superconductivity. Obviously, the oxygen atoms interstitially dissolved in the matrix have an important role in superconductivity, since they move easily in the lattice. In addition, they contribute to hole creation in the CuO 2 planes. Anelastic spectroscopy (internal friction) measurements are sensitive tools for the study of defects in solids, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The peak P3 and P4 were observed by Gimenez et al [2,11]. In BSCCO superconductors, a structural transformation occurs from the superconducting orthorhombic phase to the monoclinic non-superconducting phase (O-M phase transformation).…”
Section: Resultsmentioning
confidence: 81%
See 2 more Smart Citations
“…The peak P3 and P4 were observed by Gimenez et al [2,11]. In BSCCO superconductors, a structural transformation occurs from the superconducting orthorhombic phase to the monoclinic non-superconducting phase (O-M phase transformation).…”
Section: Resultsmentioning
confidence: 81%
“…The monoclinic phase transformation was associated with the easy diffusion of oxygen atoms out of the crystal at high temperature (350-400 o C) and high vacuum (1.5 x 10 -7 mbar), causing local distortions. Due to the local distortions, which is caused by the O-M phase transition, the peak P4 was associated with these structural phase transformations [2]. In a BSCCO lattice, additional oxygen atoms (y > 0) are found in the BiO layers in interstitial positions between two Bi atoms.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At least three maxima appear at 200, 350, and 450 K. It can be observed that the intensity of these peaks increases as the interstitial oxygen content increases. These three processes are obviously due to the interstitial oxygen [13].…”
Section: Resultsmentioning
confidence: 99%